Global characterisation factors to assess land use impacts on biotic production - Brandão, Miguel; i Canals, Llorenç Mil (The international journal of life cycle assessment, 2013)
PURPOSE: The inclusion of land-use activities in life cycle assessment (LCA) has been subject to much debate in the LCA community. Despite the recent methodological developments in this area, the impacts of land occupation and transformation on its long-term ability to produce biomass (referred to here as biotic production potential [BPP]) — an important endpoint for the Area of Protection (AoP) Natural Resources — have been largely excluded from LCAs partly due to the lack of life cycle impact assessment methods. MATERIALS AND METHODS: Several possible methods/indicators for BPP associated with biomass, carbon balance, soil erosion, salinisation, energy, soil biota and soil organic matter (SOM) were evaluated. The latter indicator was considered the most appropriate for LCA, and characterisation factors for eight land use types at the climate region level were developed. RESULTS AND DISCUSSION: Most of the indicators assessed address land-use impacts satisfactorily for land uses that include biotic production of some kind (agriculture or silviculture). However, some fail to address potentially important land use impacts from other life cycle stages, such as those arising from transport. It is shown that the change in soil organic carbon (SOC) can be used as an indicator for impacts on BPP, because SOC relates to a range of soil properties responsible for soil resilience and fertility. CONCLUSIONS: The characterisation factors developed suggest that the proposed approach to characterize land use impacts on BBP, despite its limitations, is both possible and robust. The availability of land-use-specific and biogeographically differentiated data on SOC makes BPP impact assessments operational. The characterisation factors provided allow for the assessment of land-use impacts on BPP, regardless of where they occur thus enabling more complete LCAs of products and services. Existing databases on every country’s terrestrial carbon stocks and land use enable the operability of this method. Furthermore, BPP impacts will be better assessed by this approach as increasingly spatially specific data are available for all geographical regions of the world at a large scale. The characterisation factors developed are applied to the case studies (Part D of this special issue), which show the practical issues related to their implementation.